2018
DOI: 10.1111/jns.12279
|View full text |Cite
|
Sign up to set email alerts
|

Serum and cerebrospinal neurofilament light chain levels in patients with acquired peripheral neuropathies

Abstract: Neurofilament light chain (NFL) levels reflect axonal damage in different inflammatory and neurodegenerative central nervous system conditions, in correlation with disease severity. Our aim was to determine the possible diagnostic and prognostic value of serum and cerebrospinal fluid (CSF) NFL levels in subjects with different forms of acquired peripheral neuropathies (PN). Paired serum and CSF samples of 25 patients with acquired PN were analysed for NFL using an ultrasensitive technique (Quanterix, Simoa, Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
96
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 11 publications
(19 reference statements)
11
96
3
Order By: Relevance
“…We found a correlation between sNfL levels and axonal damage assessed with NCS in CIDP patients starting IT (Figure ) in line with previous findings of sNfL levels being a reflection of neuro‐axonal damage . The correlation in our study was, however, no longer significant when corrected for age, which may be explained by the relatively small number of NCS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found a correlation between sNfL levels and axonal damage assessed with NCS in CIDP patients starting IT (Figure ) in line with previous findings of sNfL levels being a reflection of neuro‐axonal damage . The correlation in our study was, however, no longer significant when corrected for age, which may be explained by the relatively small number of NCS.…”
Section: Discussionsupporting
confidence: 91%
“…A recent small pilot study found a correlation between increased levels of sNfL and disability, using the overall neuropathy limitation scale, in patients with various acquired peripheral neuropathies including 12 CIDP patients, although specific results for CIDP patients were not reported . In our study, we did not find a correlation between sNfL levels and disability in the IT cohort at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hopefully, in the nearby future, new diagnostic tools may become available. Recently, attention has been paid to neurofilament light chain as potential marker of peripheral nerve damage both in the preclinical and clinical setting . A possible diagnostic and prognostic role of neurofilaments in the polyneuropathies workup is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%